The use and potential abuse of psychoactive plants in southern Africa: an overview of evidence and future potential - Nyazema, Norman Zimunda; Chanyandura, Jonathan Tinotenda; Egan, Bronwyn (Frontiers in Pharmacology, 2024)
In Southern Africa most of the Bantu ethnic groups utilize indigenous herbal medicines, some of which have psychoactive properties. Traditional medical practitioners, TMPs, commonly use them, not only for divinatory purposes but also for the treatment and management of mental and other illnesses. Unfortunately the research results, risks and benefits from their use do not align. Little is known about their potential abuse liability among TMPs and some members of the communities in Southern Africa. Herbal medicines are complex and their complexity comes from the fact that whole plants are sometimes used, unlike in other treatments where one active ingredient is used. However, if key mechanisms of action of these ethnomedicinal plants can be identified through socio-pharmacological research, useful botanical agents can be developed. A review of socio-pharmacological studies to evaluate consequences of exposure to ethnomedicinal plants with psychoactive properties was carried out. The aim was to identify harm reduction strategies and to investigate how the plants could be developed into useful botanicals.The search methods involved retrieval of all records from PubMed/MEDLINE, Embase, Web of Science, Dissertations and Theses Global and OpenGrey. The English Language and human subjects were used as filters. In addition, some information was obtained from TMPs and community members.The following psychoactive plants were found to be commonly used or abused, Boophone disticha, Cannabis sativa, Datura strammonium, Lenotis leonurus, Psilocybe cubensis and Sceletum tortuosum. Commercialization of Cannabis, L. leonurus, S. tortuosum, Aspalathus is growing fast. Abuse liability B. disticha, D.strammonium and P. cubensis, appeared not to be appreciated. Five countries were found to have TMP policies and 3 with TMP Councils.TMPs in the region are aware of the CNS effects of the psychoactive plants identified which can be explored further to develop therapeutic agents. There is need to work closely with TMPs to reduce harm from abuse of these plants.